Patterns of Depressive Symptoms and Social Relating Behaviors Differ Over Time From Other Behavioral Domains for Young People With Down Syndrome. Issue 19 (May 2015) - Foley, Kitty-Rose; Bourke, Jenny; Einfeld, Stewart L.; Tonge, Bruce J.; Jacoby, Peter; Leonard, Helen; Polak., Thomas
<x xml:space="preserve">Abstract</x> Abstract People with intellectual disabilities are at a higher risk for experiencing behavioral, emotional, and psychiatric problems in comparison with the general population. People with Down syndrome have been reported as experiencing fewer behavioral problems than others with intellectual disability, although still at a greater level than the non-intellectually disabled population, except for depression and Alzheimer disease. The aim of this study was to describe the trajectories of subscales of behavior, including depressive symptoms, communication disturbance, anxiety, disruptiveness, and social relating abilities, for young adults with Down syndrome. Families of young adults with Down syndrome living in Perth, Western Australia, participated in a questionnaire study over 8 years, 2004 (n = 255), 2009 (n = 191), and 2011 (n = 188). Questionnaires collected information about young person characteristics and family functioning. The parent-completed Developmental Behavior Checklist-Adult (DBC-A) and Developmental Behavior Checklist-Primary Carer Version (DBC-P) were used to measure emotional and behavioral problems. These measures include the following subscales: disruptive, communication and anxiety disturbances, self-absorbed, antisocial, depressive, and social relating. DBC score declined from 2004 to 2011 reflecting an improvement in behavior in the self-absorbed (coeff −0.011, 95% confidence interval (CI) −0.031, −0.008), anxiety (coef −0.009 95%CI −0.129, −0.006), communication disturbances (coeff −0.008, 95% CI −0.012, −0.005) and disruptive/antisocial behavior (coeff −0.013, 95% CI −0.016, −0.009) subscales. Subscales for depressive symptoms and social relating problems decreased less (coeff −0.003, 95% CI −0.007, −0.0001) (coeff −0.003 95% CI −0.007, 0.001). Young people who were lower functioning were reported as exhibiting significantly more behavioral problems across every subscale when compared with those who were higher functioning. Behavior of young adults with Down syndrome improves over time but depressive symptoms and social relating behavior problems persist into adulthood. It is possible that those with persistent depressive symptoms are at a high risk for developing depressive illness in adulthood. Identifying young people with Down syndrome who are at risk for developing depression in adult life has implications for prevention and early treatment.